DETERMINANTS THAT INFLUENCE THE ACTUAL BEHAVIOUR TO INVEST IN UNIT TRUST FUNDS: AN ANALYSIS OF THE ATTRIBUTES OF THE SALESPERSON - Richard Albert Gontusan; Caroline Geetha; Azizi @ Azaze Abdul Adis (Malaysian Journal of Business and Economics (MJBE), 2021)
Despite the inherent and much-publicised benefits of investing in unit trust funds, not everyone is investing in them. Investing in unit trust funds, which is open to everyone, offers the investor, at low risks, returns which are potentially higher than those of savings, fixed deposit or even Employees Provident Fund. The relatively higher returns from unit trust investments could help the investor secure a more financially sound future, especially when it comes to his or her retirement. Based on observations, given the same socio-economic backgrounds, some people are more willing to invest in unit trust funds compared to others. Many probable factors are influencing a person’s decision to invest in unit trust funds. Using the Theory of Planned Behaviour and Trait Theory, this study aims to identify and examine those factors, especially the role of the salesperson, which can influence the intention to invest in unit trust funds, thus contributing to the body of knowledge about the Theory of Planned Behaviour in this regards. It is hoped that the findings of this study could help unit trust companies and other relevant parties design a more effective approach in encouraging more Malaysians to invest in unit trust funds and help them secure a more financially sound future. Data will be collected through a questionnaire by way of purposive sampling. Based on Cochran’s formula, 500 questionnaires will be distributed throughout Sabah, the sample population. The Independent Variables identified are attitude, subjective norm, a salesperson’s attributes and perceived behavioural control while the dependent variable is behaviour to invest in the unit trust. A pilot study on the questionnaire, which has been converted into Google form, had been distributed. A total of 44 complete questionnaires were considered for analysis, following which all the questions contained in the questionnaire passed the Cronbach’s Alpha Test for reliability.